A Flow-based Flight Scheduler for En-route Air Traffic Management. Issue 3 (2016) - Li, Qing; Zhang, Yicheng; Su, Rong
Abstract: This paper addresses a network-wide scheduling problem for generating, adjusting and optimizing flight schedules in en-route airspace. The aim of scheduling is twofold: to support flight plans by providing flight schedules reliable on optimal flow restrictions; and to assist en-route traffic control by ensuring safe and ordered trajectory of traffic. Firstly, we design an algorithm to generate continuous-time flight schedules based on discrete-time flow assignments of aircrafts. This algorithm is further enhanced with consideration of sequence optimization for merging traffic. A flight scheduling system has been developed in a simulation environment.